Peranan Konseling Behavioral Berbasis CBT dalam Mengatasi Smartphone Addiction pada Remaja - Ilman, Ahmad Zaki; Firman, Firman; Netrawati, Netrawati (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The use of smartphones has become a primary need today, but excessive use can have a negative impact, one of which is smartphone addiction. This study aims to determine the role of Cognitive Behavioral Therapy (CBT)-based counseling in overcoming smartphone addiction in adolescents. The method used is literature review, which identifies, assesses, and interprets all findings related to the research topic to answer the research questions that have been set. International and national journals were searched online through relevant databases such as Science Direct, Pubmed, Publish or Perish, and Google Scholar. Literature searches conducted for the period 2018 to 2024 resulted in 4700 related articles, and after further searches there were 8 journal articles that were relevant to the title and research data. Based on this literature review research, the use of Cognitive Behavioral Therapy (CBT) counseling is proven to help overcome smartphone addiction in adolescents by changing negative thought patterns, unhealthy behaviors, and teaching self-control strategies.